Analisis Kebijakan Restrukturisasi Kredit Terhadap Pembiayaan Usaha Mikro, Kecil, Dan Menengah Pada Masa Pandemi Covid-19 Di Indonesia Berdasarkan Peraturan Otoritas Jasa Keuangan Nomor 48/Pojk.03/2020 (Studi Pada Dusun X Desa Medan Estate) - Ahmad Zaky Mubaraq MR Lubis (Iuris Studia: Jurnal Kajian Hukum, 2022)
POJK Number 48/POJK.03/2020 was issued by the Government as an effort to recover the national economy in the MSME sector affected by COVID-19. However, it is necessary to see whether the credit restructuring has been effective or not. The problem in this research is what is the basis for considering the implementation of a credit restructuring policy for MSMEs during the COVID-19 pandemic, how is the process of applying for credit restructuring for MSMEs during the COVID-19 pandemic based on POJK No. 48/POJK.03/2020, and what is the impact implementation of credit restructuring policies for MSMEs in Dusun X Desa Medan Estate based on OJK regulations Number 48/POJK.03/2020. The results of the study show: the basic considerations for implementing a credit restructuring policy for MSMEs during the COVID-19 pandemic considering the consequences of the hampered performance and capacity of MSME debtors in paying loan installments. The process of applying for credit restructuring for MSMEs during the COVID-19 pandemic based on POJK Number 48/POJK.03/2020 h generally refers to the POJK on asset quality assessment, but its implementation can vary and is largely determined by the policies of each bank. The impact of implementing a credit restructuring policy for MSMEs in Dusun X Desa Medan Estate based on OJK regulation Number 48/POJK.03/2020 is that MSMEs can continue to run slowly and fulfill their obligation to pay regular installments during the pandemic. However, this credit restructuring has not run effectively, because it does not cover all affected MSMEs and it is feared that it will only be temporary.